Interventions to prevent occupational noise-induced hearing loss: A Cochrane systematic review. (March 2014) - Verbeek, Jos H.; Kateman, Erik; Morata, Thais C.; Dreschler, Wouter A.; Mischke, Christina
Abstract Objective: To assess the effectiveness of interventions for preventing occupational noise exposure or hearing loss compared to no intervention or alternative interventions. Design: We searched biomedical databases up to 25 January 2012 for randomized controlled trials (RCT), controlled before-after studies and interrupted time-series of hearing loss prevention among workers exposed to noise. Study sample: We included 19 studies with 82 794 participants evaluating effects of hearing loss prevention programs (HLPP). The overall quality of studies was low to very low, as rated using the GRADE approach. Results: One study of stricter legislation showed a favorable effect on noise levels. Three studies, of which two RCTs, did not find an effect of a HLPP. Four studies showed that better use of hearing protection devices in HLPPs decreased the risk of hearing loss. In four other studies, workers in a HLPP still had a 0.5 dB greater hearing loss at 4 kHz (95% CI − 0.5 to 1.7) than non-exposed workers. In two similar studies there was a substantial risk of hearing loss in spite of a HLPP. Conclusions: Stricter enforcement of legislation and better implementation of HLPPs can reduce noise levels in workplaces. Better evaluations of technical interventions and long-term effects are needed.